Preferensi Pengguna Layanan Perpustakaan dengan Menggunakan Analisis Konjoin - Oki Dwipurwani; Dian Cahyawati S (Jurnal Penelitian Sains, 2011)
Library represent one of main indicator to support the international class university. And so it’s with Unsri have owned vision go to the international class university, so that require to prepare its library have international level. Every library service, specially the wearer service, consisted of factors as shaper, and every factor contain level-level of factor. Hence shall have knowledge preference and perception of consumer to the service, which is like what required by consumer. By using Conjoint Analysis method would have been obtained combination from level-level factor (stimuly) took a fancy by consumer according to value of highest utility from every level factor. The result show that, from 300 netted responder, 252 up to standard responder and the validity. In general the consumer wish combination library’s service in the form of making of card through email, borrowing durations of literature is two weeks, way of getting literature come direct to library, sum up literature borrowed more than 3, prolongation of borrowing literature and searching of literature information can through internet, searching of literature information to other library can through interconnection online, and support of literature information searching wish assisted by librarian.